The neotropical damselfly genus Cora: new larval descriptions and a comparative analysis of larvae of known species (Odonata: Polythoridae) - Ramírez Ulate, Luis Alonso (2011)
The final larval stadium of four species of Cora are described and compared with known species in the genus. Cora skinneri Calvert, 1907, C. semiopaca Selys, 1878 and C. lugubris Navás, 1934 are described and illustrated for the first time using material from Costa Rica for the first two and from Colombia for the latter. A redescription of C. marina Selys, 1868 from specimens collected in Costa Rica is also included for comparison. Although all species are very similar as larvae, two major groups can be differentiated based on the shape of the caudal gills. The three species here described for the first time are very similar, but can be separated from each other using a combination of characters.